2012
DOI: 10.1093/heapol/czs044
|View full text |Cite
|
Sign up to set email alerts
|

Newborn survival in Bangladesh: a decade of change and future implications

Abstract: Remarkable progress over the last decade has put Bangladesh on track for Millennium Development Goal (MDG) 4 for child survival and achieved a 40% decline in maternal mortality. However, since neonatal deaths make up 57% of under-five mortality in the country, increased scale up and equity in programmes for neonatal survival are critical to sustain progress. We examined change for newborn survival from 2000 to 2010 considering mortality, coverage and funding indicators, as well as contextual factors. The natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 43 publications
0
73
0
Order By: Relevance
“…Adults and older children benefit more from health investment and health infrastructure for example, in the Indian subcontinent, in Bangladesh, the national neonatal mortality rate has undergone an annual decline of 4.0% since 2000, reflecting greater progress than both the regional and global averages, but the mortality reduction for children 1-59 months was double this rate, at 8.6%. 10 Bangladesh spent 19 $ per capita or 3.5% of its GDP on health. Similarly in Nepal, neonatal mortality rate reduced by 3.6% per year, which was faster than the regional average (2.0%) but slower than national annual progress for mortality of children aged 1-59 months (7.7%) and maternal mortality (7.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Adults and older children benefit more from health investment and health infrastructure for example, in the Indian subcontinent, in Bangladesh, the national neonatal mortality rate has undergone an annual decline of 4.0% since 2000, reflecting greater progress than both the regional and global averages, but the mortality reduction for children 1-59 months was double this rate, at 8.6%. 10 Bangladesh spent 19 $ per capita or 3.5% of its GDP on health. Similarly in Nepal, neonatal mortality rate reduced by 3.6% per year, which was faster than the regional average (2.0%) but slower than national annual progress for mortality of children aged 1-59 months (7.7%) and maternal mortality (7.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization (WHO) has published guidelines for Essential Newborn Care (ENC) including protective practices before, during, and after birth [3]. Several South Asian countries have increased the number of women giving birth in institutions or at home with a skilled birth attendant (SBA) [4-6]. Increasing access to skilled attendance at birth can reduce both maternal and neonatal mortality, but in resource-poor areas, having a skilled birth attendant or an institutional delivery may not guarantee full provision of WHO-recommended essential newborn care [7-12].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing access to skilled attendance at birth can reduce both maternal and neonatal mortality, but in resource-poor areas, having a skilled birth attendant or an institutional delivery may not guarantee full provision of WHO-recommended essential newborn care [7-12]. Increased access to some components of newborn care for women giving birth at home without a SBA can also be an effective strategy to reduce neonatal morbidity and mortality [5,6,13], for instance through the use of clean delivery kits [14,15]. Both strategies are based on the knowledge that increasing the coverage of essential newborn care practices in South Asia is essential to achieving the millennium development goals for child survival [16-18].…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in Dhaka slums showed sepsis as a direct cause of neonatal deaths in 20% cases 8 . In another study in Bangladesh, estimated causes of mortality around the year 2010 for 102,000 neonatal deaths showed that severe infections (sepsis, meningitis, pneumonia and tetanus) contributed 20% of neonatal deaths 9,10 .…”
Section: Epidemiology and Public Health Issuesmentioning
confidence: 99%